Enhancing early-stage chilling tolerance [Sorghum bicolor (L.) Moench] by integrating physiological and genetic approaches - Ostmeyer, Troy (Kansas State University, 2020)
Grain sorghum (Sorghum bicolor L. Moench) is an important grain crop in the United States. Early planting can help to extend sorghum’s growing season and increase planting area and production, but is poorly adapted to chilling temperatures (<15°C) because of its tropical origin. Earlier planting could have additional advantages, which include effective utilization of early spring soil moisture as well as earlier canopy cover to reduce weed pressure and evaporation losses. Developing sorghum hybrids with early-stage chilling tolerance has been one of the major goals for the private and public sectors in the U.S. and elsewhere. However, with sorghum’s tropical adaptation, chilling temperatures pose serious challenges to obtain uniform emergence, maintaining good plant stand, and early seedling vigor. Therefore, it is important to understand the inheritance of seedling and agronomic traits and to select the most appropriate parental lines and hybrids with the highest degree of early-stage chilling tolerance. The objectives of this project were: (i) to estimate the general and specific combining ability of 27 newly developed sorghum hybrids and their 12 parental lines over two years in the field; and (ii) to phenotype a subset of the original population, including the four most promising chilling tolerant hybrids, their five parental lines and three checks in field and controlled environment chamber conditions. To impose chilling stress in the field, the genotypes were planted 1.5 months ahead (mid-April) of current agronomic practices of sorghum production in Kansas followed with a regular planting (end of May) at the Agricultural Research Center, Hays, Kansas in 2018 and 2019. In the controlled environment chambers, the genotype subset were exposed to three temperature treatments, which included a constant chilling stress (current chilling tolerance screening practice), a field-like gradual increase in temperature (improved chilling tolerant screening) and a control treatment (optimal temperatures). Plants grown under early-stage chilling stress showed a significant decrease in seedling emergence and vigor. Chilling stress also delayed time until flowering and maturity compared to control. However, it did not negatively affect the final yield or grain quality. From this study, we observed that early planting has the potential to increase vegetative growth and grain filling duration. The tannin-free hybrid, ARCH11192A/ARCH12012R, had the highest potential for early planting. Overall, heterosis was shown to be beneficial in plant stand and seedling vigor as well as final grain yield for early planting. Developing early-stage chilling tolerant hybrids with the ability to emerge, develop, and out-yield currently available hybrids will pave the way to increasing grain sorghum productivity.
Keywords: Agronomy; Sorghum; Chilling tolerance; Early planting; Hybrids; Phenotyping